1977
DOI: 10.1042/bj1650295
|View full text |Cite
|
Sign up to set email alerts
|

Effects of proteolytic digestion by chymotrypsin on the structure and catalytic properties of reduced nicotinamide–adenine dinucleotide–ubiquinone oxidoreductase from bovine heart mitochondria

Abstract: 1. Incubation of NADH-ubiquinone oxidoreductase (Complex I) with chymotrypsin caused loss of rotenone-sensitive ubiquinone-1 reduction and an increase in rotenone-insensitive ubiquinone reduction. 2. Within the same time-course, NADH-K(3)Fe(CN)(6) oxidoreductase activity was unaffected. 3. Mixing of chymotrypsin-treated Complex I with Complex III did not give rise to NADH-cytochrome c oxidoreductase activity. 4. Gel electrophoresis in the presence of sodium dodecyl sulphate revealed selective degradation of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
9
0

Year Published

1978
1978
1995
1995

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…Obvious possibilities are that such lipid-protein interactions are required for the conformational stability of Complex I. It has been shown that lipid depletion leads to changes in the midpoint potential of the non-haem-iron centre 2 (Ohnishi et al, 1974) and to greater susceptibility of the enzyme to proteolytic digestion (Ragan, 1976b;Crowder & Ragan, 1977). The experiments with dimyristoyl-sn-glycero-3-phosphocholine did not provide any evidence that freezing the annular and extraannular lipid directly affected activity through the protein conformation.…”
Section: Discussionmentioning
confidence: 99%
“…Obvious possibilities are that such lipid-protein interactions are required for the conformational stability of Complex I. It has been shown that lipid depletion leads to changes in the midpoint potential of the non-haem-iron centre 2 (Ohnishi et al, 1974) and to greater susceptibility of the enzyme to proteolytic digestion (Ragan, 1976b;Crowder & Ragan, 1977). The experiments with dimyristoyl-sn-glycero-3-phosphocholine did not provide any evidence that freezing the annular and extraannular lipid directly affected activity through the protein conformation.…”
Section: Discussionmentioning
confidence: 99%
“…When complex I was subjected to proteolytic digestion, the NADH-ubiquinone reductase activity disappeared when peptides with molecular masses of 49,000, 42,000, 39,000, 26,000, 23,500, 18,000, and 15,500 were released [5], NADH-potassium ferricyanide reductase activity disappeared when the 53,000 molecular mass peptide was re leased [5], Loss of FMN during autolysis may be involved. Rouslin et al [33] showed that after 60 min of autolysis the acid-extractable FMN was 58% of the control values.…”
Section: Discussionmentioning
confidence: 99%
“…One-dimensional SDS/polyacrylamide-gel electrophoresis Separation on gels (12cmx4mm internal diam.) containing 12.5% (w/v) acrylamide and 0.34% bisacrylamide was as described by Crowder & Ragan (1977), by the procedure of Weber & Osborn (1969). Alternatively, two discontinuous systems were used.…”
Section: Biological Preparationsmentioning
confidence: 99%
“…However, this enzyme is far and away the most complicated, since purified preparations may be resolved into at least 16 components when analysed by conventional gel electrophoresis in the presence of SDS (Ragan, 1976). Analysis by discontinuous gel electrophoresis increased the number of resolvable components to 18 (Crowder & Ragan, 1977). These results are broadly in agreement with the findings of others (Hare & Crane, 1974;Dooijewaard et al, 1978a,b), although it is obvious from the literature that the number of polypeptides reported is merely a function of the resolving power of the analytical system used.…”
mentioning
confidence: 99%